"Misunderstood... not badly behaved." The Experiences of Young People Excluded from School" - Kirsty, Jones (2014)
Abstract Young people who may be at risk of or experience school exclusion have been discussed in the literature extensively across many disciplines: psychology, sociology, education, health and in policy. Multiple risk factors have been identified but there is a distinctive lack of studies identifying what young people themselves view as the reasoning behind their exclusion. The following study was a narrative inquiry undertaken using the method of qualitative semi-structured interviews and analysed from an Interpretative Phenomenological Analysis approach. Three young people aged 15 years: two female, one male and of varying identified ethnic backgrounds were interviewed. The superordinate themes identified were: social explanations of exclusion, psychological explanations of exclusion and interventions that would help other young people. The nested themes included: family, peers at school, mental health, personality, identity and behaviour, aspiration, lack of trust in authority, education and other support. Overall, the analysis revealed that these young people had complex social backgrounds and may have experienced multiple traumas and deprivation. This has implications for those working in health, social and educational professions as these young people would have benefited from accessing services, particularly in the early years.